2010
DOI: 10.1016/j.ymgme.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an MPS I-H knock-in mouse that carries a nonsense mutation analogous to the human IDUA-W402X mutation

Abstract: Here we report the characterization of a knock-in mouse model for the autosomal recessive disorder mucopolysaccharidosis type I-Hurler (MPS I-H), also known as Hurler syndrome. MPS I-H is the most severe form of α-L-iduronidase deficiency. α-L-iduronidase (encoded by the IDUA gene) is a lysosomal enzyme that participates in the degradation of dermatan sulfate and heparan sulfate. Using gene replacement methodology, a nucleotide change was introduced into the mouse Idua locus that resulted in a nonsense mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 48 publications
8
70
0
Order By: Relevance
“…IDUA encodes a glycosyl hydrolase that hydrolyzes the terminal alpha-L-iduronic acid residues of two glycosaminoglycans, dermatan sulfate and heparan sulfate (49) . Wang et al (2010) (50) created Idua-W392X mouse model, and found that 35-week-old homozygous Idua-W392X mice showed a 24% increase in femur BMD, and bone abnormalities such as thickening of the zygomatic arch and aberrations in the length and width of the femur were also observed (50) .…”
Section: Discussionmentioning
confidence: 99%
“…IDUA encodes a glycosyl hydrolase that hydrolyzes the terminal alpha-L-iduronic acid residues of two glycosaminoglycans, dermatan sulfate and heparan sulfate (49) . Wang et al (2010) (50) created Idua-W392X mouse model, and found that 35-week-old homozygous Idua-W392X mice showed a 24% increase in femur BMD, and bone abnormalities such as thickening of the zygomatic arch and aberrations in the length and width of the femur were also observed (50) .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one knock-in mouse model has been reported for the diseases studied herein [55]. Interestingly, in this particular model (mutation p.Trp392* of IDUA;…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the two previously reported Idua knock-out mouse models, Idua −/− and MPS I [13], [14], the Idua- W392X knock-in mouse model carries a nonsense mutation corresponding to the IDUA- W402X mutation, commonly found in Hurler syndrome patients [15]. Wang et al showed that the phenotype of Idua- W392X mouse model parallels that of human MPS I-H disease, which includes GAG accumulation due to loss of α-L-iduronidase activity, cardiac manifestations and bone abnormalities such as broadening of the face, thickening of the zygomatic arch and atypical femur length and width [15].…”
Section: Introductionmentioning
confidence: 67%
“…Wang et al showed that the phenotype of Idua- W392X mouse model parallels that of human MPS I-H disease, which includes GAG accumulation due to loss of α-L-iduronidase activity, cardiac manifestations and bone abnormalities such as broadening of the face, thickening of the zygomatic arch and atypical femur length and width [15]. Even though the existing animal models have been useful in evaluating various therapeutic approaches such as enzyme replacement therapy [16], bone marrow transplantation [17], [18], and gene therapy [19], [20], much of the molecular mechanisms leading to the pathology remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%